2016
DOI: 10.4995/agt.2016.4616
|View full text |Cite
|
Sign up to set email alerts
|

The equivalence of two definitions of sequential pseudocompactness

Abstract: We show that two possible definitions of sequential pseudocompactness are equivalent, and point out some consequences.2010 MSC: Primary 54D20; Secondary 54B10.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…2 One of the authors introduced this notion a few years ago as a natural property intermediate between feeble and sequential compactness, which may be useful in some applications in topological algebra. Indeed, for instance, Proposition 1.10. by Artico et al [4] combined with Theorem 1.1 by Lipparini [17] states that that each T 0 feebly compact topological group is sequentially feebly compact. But later we found that it is a known property, even with the same name.…”
Section: Definitions and Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 One of the authors introduced this notion a few years ago as a natural property intermediate between feeble and sequential compactness, which may be useful in some applications in topological algebra. Indeed, for instance, Proposition 1.10. by Artico et al [4] combined with Theorem 1.1 by Lipparini [17] states that that each T 0 feebly compact topological group is sequentially feebly compact. But later we found that it is a known property, even with the same name.…”
Section: Definitions and Relationsmentioning
confidence: 99%
“…In general topology we often investigate different classes of compact-like spaces and relations between them, see, for instance, basic [11,Chap. 3] and general works [9], [19], [23], [22], [17]. We consider the present paper as a next small step in this quest.…”
Section: Definitions and Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…También, S. García-Ferreira y A. H. Tomita muestran en [20] la existencia de un espacio secuencialmente pseudocompacto que no es secuencialmente compacto. P. Lipparini demuestra en [25] que la propiedad (P) es equivalente a la siguiente propiedad en la clase de espacios topológicos: (P 0 ) Para toda sucesión hU n i de conjuntos abiertos no vacíos de X, existe un subconjunto infinito J ⇢ ! y un punto p 2 X tal que el conjunto {n 2 J : W \ U n = ;} es finito para toda vecindad W de p.…”
Section: Capítulo 4 Espacios Secuencialmente Tenuemente Compactosunclassified